Air pollution control intensity and ecological total-factor energy efficiency: The moderating effect of ownership structure. (10th June 2018) - Wang, Qian; Yuan, Baolong
Abstract: To improve China's industrial ecological total-factor energy efficiency is an important issue that attracts widespread attention from researchers and policymakers. This paper uses the panel data of 37 subsectors of China's industrial sector from 2003 to 2014 to examine the influence of air pollution control on ecological total-factor energy efficiency and the moderating effect of ownership structure. Furthermore, based on the intensity of air pollution, the industrial sector is divided into high-polluting industries, medium-polluting industries and low-polluting industries so that the industrial heterogeneity can be analyzed. The results show that, (1) in the short term, air pollution control has a significant inhibiting effect on industrial ecological total-factor energy efficiency. In the long run, the influence of air pollution control on industrial ecological total-factor energy efficiency is significantly heterogeneous. In high-polluting industries, the negative influence of air pollution control on industrial ecological total-factor energy efficiency is not significant, but in medium-polluting industries and low-polluting industries, the negative influence is obvious. (2) State-owned enterprises have a significantly inhibiting effect on industrial ecological total-factor energy efficiency, that is, the expansion of state-owned enterprises will adversely affect industrial energy conservation and emission reduction. (3) Overall, the moderating effect of ownership structure on the relationship between air pollution control and ecological total-factor energy efficiency is not significant. However, for certain industries, the moderating effect of ownership structure is significant. Specifically, the effect is significantly positive in high-polluting industries, significantly negative in medium-polluting industries for a short term, and significantly negative in low-polluting industries for a long term. Finally, this paper puts forward specific policy suggestions.